Chemical Compound Analysis and Antibacterial Effect of Five Medicinal Plants Essential Oils on Infectious Bacteria - Hassan Habibi; Najmeh Ghahtan; Leila Karami (Shiraz University of Medical Sciences, 2018)
Fundamental research on plants in order to identify their pharmaceutical agents and their effects on pathogens has been increased in medicinal plant research centers around the world, especially in Iran. This study has been conducted to determine the antibacterial effects of Pulicaria gnaphalode, Ducrosia anethifolia, Trachyspermum copticum, Foeniculul vulgare Mill, and Majorana hortensis Minch essential oils on Proteus vulgaris, Pseudomonas aeruginosa, and Shigella boydii. Their essential oils were extracted by a Clevenger apparatus after plants powder preparation in appropriate condition. Gas chromatography-mass spectrometry (GC-MS) was used for essential oils (EOs) chemical analysis. Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) were also investigated for studying the EOs effect on bacteria. Sixty three compounds were identified in the EOs analysis of five plants by GC-MS. All EOs tested in this study showed antibacterial properties on all three bacterial strains. EO of the Trachyspermum copticum showed more antibacterial effects in comparison to other herbs. It is notable that there was a significant difference between the antibacterial activities of the EOs. The results of this study provide a scientific basis for using these plants in traditional home remedies. On the other hand, extraction and purification of these EOs can provide more phytochemicals with stronger antibiotic properties.